Question
upstudy study bank question image url

B: For each pair of simultaneous equations: \begin{tabular}{|l|}\hline\( x+y=13 \) and \( 8 x-5 y=0 \) \\ \( x+y=21 \) and \( 13 x-8 y=0 \)\end{tabular} 1. Solve for \( x \) and \( y \). 2. Find the value of the ratio \( \frac{x}{y} \). Write the ratio \( \frac{x}{y} \) in decimal form correct to three decimal places where possible. 3.

Ask by Ford Hall. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

For the first pair: - x = 5, y = 8, and x/y = 0.625. For the second pair: - x = 8, y = 13, and x/y ≈ 0.615.

Solution

We are given two pairs of simultaneous equations. Case 1:   Equation 1: x + y = 13   Equation 2: 8x – 5y = 0 Step 1: Solve Equation 1 for y:   y = 13 – x Step 2: Substitute y in Equation 2:   8x – 5(13 – x) = 0   8x – 65 + 5x = 0   13x – 65 = 0   13x = 65   x = 65 ÷ 13 = 5 Step 3: Find y:   y = 13 – 5 = 8 Step 4: Find the ratio x/y:   x/y = 5/8 = 0.625 Case 2:   Equation 1: x + y = 21   Equation 2: 13x – 8y = 0 Step 1: Solve Equation 1 for y:   y = 21 – x Step 2: Substitute y in Equation 2:   13x – 8(21 – x) = 0   13x – 168 + 8x = 0   21x – 168 = 0   21x = 168   x = 168 ÷ 21 = 8 Step 3: Find y:   y = 21 – 8 = 13 Step 4: Find the ratio x/y:   x/y = 8/13   Using division: 8 ÷ 13 ≈ 0.615 (to three decimal places) Thus, the answers are: For the first pair of equations:   x = 5, y = 8, and x/y = 0.625. For the second pair of equations:   x = 8, y = 13, and x/y ≈ 0.615.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the simultaneous equations, let's start with the first pair: 1. For the equations \( x+y=13 \) and \( 8x-5y=0 \): From \( x+y=13 \), we can express \( y = 13 - x \). Substitute \( y \) into the second equation: \( 8x - 5(13 - x) = 0 \) This simplifies to \( 8x - 65 + 5x = 0 \) or \( 13x = 65 \). Thus, \( x = 5 \). Now substitute back to find \( y \): \( y = 13 - 5 = 8 \). So, \( (x, y) = (5, 8) \). 2. The ratio \( \frac{x}{y} \): Using the values obtained, we find \( \frac{x}{y} = \frac{5}{8} = 0.625 \) (correct to three decimal places). Now let's move on to the second pair of equations: 1. For \( x+y=21 \) and \( 13x-8y=0 \): From \( x+y=21 \), express \( y = 21 - x \). Substitute \( y \) into the second equation: \( 13x - 8(21-x) = 0 \) This simplifies to \( 13x - 168 + 8x = 0 \) or \( 21x = 168 \). Thus, \( x = 8 \). Now substitute back to find \( y \): \( y = 21 - 8 = 13 \). So, \( (x, y) = (8, 13) \). 2. The ratio \( \frac{x}{y} \): Now with these values, \( \frac{x}{y} = \frac{8}{13} \approx 0.615 \) (correct to three decimal places). In summary: For the first pair, \( (x, y) = (5, 8) \) yields a ratio of \( 0.625 \). For the second pair, \( (x, y) = (8, 13) \) gives a ratio of \( 0.615 \).

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy